An Intron 9 CYP19 Gene Variant (IVS9+5G>A), Present in an Aromatase-Deficient Girl, Affects Normal Splicing and Is Also Present in Normal Human Steroidogenic Tissues - Saraco, Nora Isabel (2015)
Background/Aims: Splicing CYP19 gene variants causingaromatase deficiency in 46,XX disorder of sexual development(DSD) patients have been reported in a few cases. Amisbalance between normal and aberrant splicing variants was proposed to explain spontaneous pubertal breast developmentbut an incomplete sex maturation progress. Theaim of this study was to functionally characterize a novelCYP19A1 intronic homozygote mutation (IVS9+5G>A) in a46,XX DSD girl presenting spontaneous breast developmentand primary amenorrhea, and to evaluate similar splicing variant expression in normal steroidogenic tissues. Methods:Genomic DNA analysis, splicing prediction programs,splicing assays, and in vitro protein expression and enzymeactivity analyses were carried out. CYP19A1 mRNA expressionin human steroidogenic tissues was also studied. Results:A novel IVS9+5G>A homozygote mutation was found.In silico analysis predicts the disappearance of the splicingdonor site in intron 9, confirmed by patient peripheral leukocytecP450arom and in vitro studies. Protein analysisshowed a shorter and inactive protein. The intron 9 transcriptvariant was also found in human steroidogenic tissues.Conclusions: The mutation IVS9+5G>A generates a splicingvariant that includes intron 9 which is also present in normalhuman steroidogenic tissues, suggesting that a misbalancebetween normal and aberrant splicing variants might occurin target tissues, explaining the clinical phenotype in the affectedpatient.